2015
DOI: 10.1371/journal.pone.0144571
|View full text |Cite
|
Sign up to set email alerts
|

Y-27632, a ROCK Inhibitor, Promoted Limbal Epithelial Cell Proliferation and Corneal Wound Healing

Abstract: Transplantation of ex vivo cultured limbal epithelial cells is proven effective in restoring limbal stem cell deficiency. The present study aimed to investigate the promoting effect of Y-27632 on limbal epithelial cell proliferation. Limbal explants isolated from human donor eyes were expanded three weeks on culture dishes and outgrowth of epithelial cells was subsequently subcultured for in vitro experiments. In the presence of Y-27632, the ex vivo limbal outgrowth was accelerated, particularly the cells with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
37
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 44 publications
6
37
1
Order By: Relevance
“…Consistent with previous studies [2527], it was found that inhibition of ROCK activity using Y-27632 increased the rate of healing of mouse corneal epithelial cells, whereas inhibition of JNK using SP600125 (as described in the Materials and methods section) decreased the rate of wound healing (mean ± s.e.m. ; SP600125 7.99 µm h −1  ± 0.95; DMSO 14.13 µm h −1  ± 1.14; t -test: p  = 0.001; n  = 7; 8: Y-27632 26.06 ± 1.53; control 16.50 ± 2.02; t -test: p  = 0.001; n  = 11; 9; figure 3 c,d ).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Consistent with previous studies [2527], it was found that inhibition of ROCK activity using Y-27632 increased the rate of healing of mouse corneal epithelial cells, whereas inhibition of JNK using SP600125 (as described in the Materials and methods section) decreased the rate of wound healing (mean ± s.e.m. ; SP600125 7.99 µm h −1  ± 0.95; DMSO 14.13 µm h −1  ± 1.14; t -test: p  = 0.001; n  = 7; 8: Y-27632 26.06 ± 1.53; control 16.50 ± 2.02; t -test: p  = 0.001; n  = 11; 9; figure 3 c,d ).…”
Section: Resultssupporting
confidence: 90%
“…We also pharmacologically inhibited two downstream mediators of PCP signalling, ROCK and JNK, and found that neither prevented wound healing. Consistent with previous data [27], ROCK inhibition increased the rate of wound healing, associated with disruption of the cytoskeleton leading to apparent stretching of cells behind the wound edge. Together with the observation that the actin cytoskeleton was not grossly defective in Vangl2-deleted corneal epithelial cells, these data suggest that reorganization of the actin cytoskeleton (the primary role of ROCK in this system) is not the main mechanism through which PCP acts during the wound-healing migration response.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…To investigate the transcriptional profile of CD109 + and CD200 + cells, expression of putative LSC markers ΔNp63, ABCB5, C/EBPδ, BMI1, AXIN2, FZD7, CHD3, WNT7A, CK14, and CK15 [12,16,[39][40][41][42][43], corneal epithelial differentiation marker CK3 [44] and marker of proliferative cells Ki67 [45] was assessed by qRT-PCR.…”
Section: The Expression Of Lsc Markers In the Cd109 And Cd200 Positivmentioning
confidence: 99%
“…34 Recent success in the isolation and expansion of primary human corneal epithelial cells has allowed for a reliable and reproducible source of primary human corneal epithelial cells for the development of novel organotypic corneal tissue models. 35,36 Primary cultured human corneal epithelial cells grown on permeable supports can address questions concerning drug transport mechanisms by avoiding species extrapolation and the influence of modified gene expression due to cell immortalization. 27,37 These model systems can be valuable for corneal penetration studies since they allow high sample throughput, access to both the apical and basolateral sides, and A to B and also B to A transport studies.…”
mentioning
confidence: 99%